Cataract Surgery in HIV Seropositive Patients: Long-Term Follow-Up. (3rd April 2019) - Accorinti, Massimo; Cecere, Michela; Scala, Andrea; Pirraglia, Maria Pia
ABSTRACT: Purpose : To study epidemiology and clinical findings of cataract in HIV+ patients. Methods : A total of 32 HIV+ patients, 11 with uveitis/retinitis before surgery and 21 without, mean follow-up 44.9 ± 36.6 months, and 114 HIV- patients, 57 with uveitis/retinitis before surgery and 57 without, were retrospectively compared. Results : Visual acuity improved in all HIV+ patients ( p  < 0.001), who were younger ( p  = 0.01) and more frequently males ( p  = 0.027). HIV+ patients with uveitis prior surgery improved less ( p  = 0.046) than HIV- ( p  < 0.001); their anterior chamber inflammation was similar to baseline. Male sex ( p  = 0.005), younger age ( p  < 0.001), dyslipidaemia ( p  = 0.058), HBV+ ( p  = 0.037), and unilateral cataract ( p  = 0.001) were more frequent in HIV+ patients with senile cataract, but they showed the same postoperative course as HIV- patients. Conclusion : Cataract surgery in HIV+ patients is safe and effective. Uveitis prior to surgery did not significantly affect the postoperative course. Systemic comorbidities are more frequent in HIV+ patients with senile cataract than in HIV- subjects.